New species and records of Amphichroum Kraatz, 1857 from China and the Himalayan Region (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2022)
New taxonomic, diagnostic and faunistic data for eight species of the genus Amphichroum Kraatz, 1858 (Omaliinae) from China and the Himalayan Region are provided. Three species are (re-) described and illustrated: A. discolor sp.n. and A. grandidentatum sp.n. (both from Biluo Mts., Yunnan, China), and A. reticulatum Coiffait, 1978 (Bhutan). New records for five species from China and Nepal are given.